The Evolution of Human Sociality. Categorizations, Emotions, and Friendship - Michael Windzio (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
This overview describes the ambivalent result of humans' evolution towards a~social and cooperative species. The evolution of friendship, based on commitment rituals and norms, solved the problem of defection in reciprocal altruism. The social brain implies the cognitive capacity of "mentalizing" and of keeping track of the reputation of group members, but, equally as importantly, generates strong emotions depending on the degree of social integration or social exclusion. Strong emotions linked to categories of social relationships, in particular to friends who we regard as almost irreplaceable, generate commitment and reduce social transactions costs and thereby facilitate cooperation. A~multilevel perspective on social categorizations reveals, however, that a~similar mechanism applies between cultural groups, owing to cultural group-level selection. Humans apply categorical distinctions within and between groups. They distinguish in-group and out-group members by cultural markers, and, in addition, between friends and others. In this perspective, cultural markers generate categorizations and emotions that facilitate unconditional support if required, but can also result in out-group rejection, and, in combination with neurochemicals, in dehumanization as well.
Keywords: 300; Friendship; Social brain; Culture; Commitment; Out-group rejection; Freundschaft; Soziales Gehirn; Kultur; Bindung; Ablehnung der Fremdgruppe